SAT0286 Serum Immunoglobulin Free Light Chain Assessment in Psoriatic Arthritis. (23rd January 2014) - Assmann, G.; Zinke, S.; Ney, J. T.; Ong, M. F.; Neumann, F.; Nold, S.; Pfreundschuh, M.
Abstract : Background: Elevation of free light chains (FLC) represents B cell activation and has been detected in the autoantibodies positive rheumatologic disorders such as rheumatoid arthritis (RA) and Sjögren syndrome. Psoriatic arthritis (PsA) is typically not accompanied by autoantibodies, however, B cells have been found in PsA synovium (Ref1 ). Objectives: We have conducted a case control study to evaluate the frequency of elevated serum FLC free kappa and free lamda levels in 210 PsA patients to detect polyclonal or monoclonal aberration. Methods: Serum FLC levels were measured using the Freelite immunoassay (The Binding Site, Germany) to detect free kappa (normal range 3.3-19.4 mg/l) and lamda (5.7-26.3). Increased free kappa and free lamda levels were defined as polyclonal, a kappa/lamda ratio <0.26 or >1.65 was defined as monoclonal aberration. As controls served healthy controls (n=50), RA patients (n=75) and B-NHLymphoma (n=288). A subgroup analysis was performed after stratification of PsA patients into age, disease duration, development of joint erosions, biological treatment, elevated TNF alpha serum levels. Results: PsA patients showed significantly less frequently polyclonal respectively monoclonal increase of FLC (7.1 and 3.8%) compared to RA (10.7 and 10.7%, **p=0.001) and B-NHLymphoma (11.5 and 10.1%, ***p=0.001), but more than in healthy controls (*p=0.001, figure 1 ). PsA patients with increased TNF alpha serum levels and patients with erosive joint disease had significantly more frequently polyclonal aberrations. Image/graph: Conclusions: Subgroups of PsA patients showed polyclonal aberrations measured by serum FLC indicating B cell activation in the course of disease. References: Cantete JD, et al. Ectopic lymphoid neogenesis in psoriatic arthritis. ARD 2007;66, 720-26 Disclosure of Interest: G. Assmann Grant/research support from: THE BINDING SITE, Schwetzingen, Germany, put the FREELITE immunoassay at costfree disposal for G Assmann, S. Zinke: None Declared, J. T. Ney: None Declared, M. F. Ong: None Declared, F. Neumann: None Declared, S. Nold: None Declared, M. Pfreundschuh: None Declared